Earthquake failure mode and collapse fragility of a 1000 kV outgoing line frame considering interactions in the tower line system. (October 2020) - Gong, Jun; Zhi, Xudong
Abstract: This study investigated the seismic responses, earthquake failure modes, and collapse fragility of a 1000 kV outgoing line frame (OLF1000, a supporting-equipment structure used in substations), by considering the interactions in the tower line system (ITLS). First, three analytical models of the OLF1000 were established, in which transmission lines were represented as massless springs based on their dynamic stiffness, and the lattice transmission tower was simplified to an elastic beam tower. Additionally, 40 real seismic records with similar spectral characteristics were used to analyze the seismic responses of the OLF1000 by considering the ITLS under minor, moderate, major and extremely major earthquakes. Moreover, a time history analysis was carried out to investigate the failure modes, and the collapse risk of the OLF1000 was considered from a probabilistic perspective. According to our results, the OLF1000 remains mostly elastic under minor and moderate earthquakes, as the energy consumption and elastic constraints of the transmission lines reduce the seismic response of the OLF1000. However, amplification of excitations by the transmission tower increases the previously reduced responses. Additionally, in the case of major and extremely major earthquakes, when considered in isolation, the OLF1000 remains intact or is only slightly damaged, but it becomes seriously damaged and can even collapse when the ITLS is considered. Furthermore, the failure mode of the OLF1000 is that of an in-plane global collapse, whereas the inclusion of the ITLS in the model suggests that an out-of-plane continuous collapse will be caused by a local failure. The ITLS significantly reduces the collapse load of the OLF1000. Finally, the ITLS substantially increases the probability of collapse of the OLF1000 under strong earthquakes.